Improved control of blood pressure and albuminuria among patients with type-2 diabetes in Finnish open care. (4th March 2017) - Varis, Juha; Metsärinne, Kaj; Koivisto, Veikko; Niskanen, Leo; Rissanen, Aila; Virkamäki, Antti; Appelroth, Tina; Pöntynen, Nora; Poussa, Tuija; Kantola, Ilkka
Abstract: Risk of cardiovascular events within the diabetic population has decreased and survival increased with patients living longer and thus facing the development of end-stage renal disease (ESRD). This calls for good care of patient with diabetes with a focus on hypertension. Patient data were collected from 42 Finnish primary care centres. Each was asked to enrol 10–12 consecutive patients with type-2 diabetes between March 2011 and August 2012. Along with the office blood pressure measurements and laboratory tests, the presence of albuminuria was measured and glomerular filtration rate estimated (eGFR). The 2013 ESH criteria for diabetic hypertensive patients (<140/85 mmHg) was reached by 39% of all 625 study patients and 38% of the pharmacologically treated 520 patients. The absence of detectable albumin in urine was significantly associated with the control of systolic blood pressure and achievement of treatment goals. Beta blockers were the most common antihypertensive agents and patients treated with them had lower eGFR compared to those not treated with these agents. The blood pressure of patients was not in full concordance with the present guideline recommendations. However, satisfactory improvement in blood pressure control, reduction of albuminuria and hence ESRD prevention was achieved.